Systematic Review and Meta-Analysis of Correlates of FFMQ Mindfulness Facets - Mattes, Josef (Frontiers in Psychology, 2019)
Background: A number of meta-analyses of mindfulness have been performed, but few distinguishes between different facets of mindfulness, despite it being known that facets of mindfulness behave differently in different populations; and most study the outcome of interventions, which tend to involve other ingredients besides mindfulness. In addition, there has recently been some concern regarding possible publication bias in mindfulness research. Objective: Systematic review and meta-analysis of the relationship of different facets of mindfulness with various outcomes, taking into account possible moderators, and controlling for publication bias using a method appropriate given the substantial heterogeneity present. Methods: Random effects meta-analysis with a number of robustness checks and estimation of the possible impact of publication bias on the results. Included are all studies that report correlations of outcomes with all five FFMQ facets, in English, French, German, or Spanish, with no restrictions on participants. Study registration: PROSPERO International prospective register of systematic reviews http://www.crd.york.ac.uk/PROSPERO/display_record.asp?ID=CRD42016041863 Data availability: Data and scripts used can be downloaded at the authors homepage and are included as supplementary material. Results: For the designated primary measure (SWLS) estimated correlations were: 0.15 [0.07, 0.22] for the Observing facet, 0.31 [0.27, 0.36] for Describing, 0.35 [0.31, 0.38] for Acting-with-Awareness, 0.30 [0.10, 0.47] for Non-judging and 0.28 [0.18, 0.37] for Non-reacting. Grouping all desirable outcomes together, Describing has the highest zero-order (though not partial) correlation; Non-judging the highest effect on avoiding undesirable outcomes. Results seem to be reasonably robust even to severe publication bias.